2017
DOI: 10.1177/1098612x17706467
|View full text |Cite
|
Sign up to set email alerts
|

Feline leprosy due to Candidatus ‘Mycobacterium tarwinense’: Further clinical and molecular characterisation of 15 previously reported cases and an additional 27 cases

Abstract: Candidatus 'M tarwinense', a fastidious member of the M simiae complex, is capable of causing feline leprosy with a tendency to produce lesions on the head, particularly involving the eyes and periocular skin. The disease has an indolent clinical course and generally responds favourably to therapy despite lesions often containing large numbers of organisms. Detailed genomic analysis may yield clues as to the environmental niche and culture requirement of this elusive organism. Prospective treatment trials and/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 45 publications
0
23
0
2
Order By: Relevance
“…Differenzialdiagnostisch kommen als Erreger der beschriebenen Hautveränderungen M. visibile, M. lepraefelis und M. tarwinense in Betracht (25), ebenso die Erreger aus der Gruppe der atypischen, nichttuberkulösen Mykobakterien und der Tuberkulose (8,18). Aufgrund der Zoonosegefahr einiger dieser Mykobakterien (8,18) sowie für Therapie und Prognose ist eine Erregerspezifizierung unabdingbar (18).…”
Section: Therapie Und Verlaufunclassified
See 1 more Smart Citation
“…Differenzialdiagnostisch kommen als Erreger der beschriebenen Hautveränderungen M. visibile, M. lepraefelis und M. tarwinense in Betracht (25), ebenso die Erreger aus der Gruppe der atypischen, nichttuberkulösen Mykobakterien und der Tuberkulose (8,18). Aufgrund der Zoonosegefahr einiger dieser Mykobakterien (8,18) sowie für Therapie und Prognose ist eine Erregerspezifizierung unabdingbar (18).…”
Section: Therapie Und Verlaufunclassified
“…Eine Diagnosestellung mittels Kultur ist möglich (8). In aktuellen Studien waren jedoch alle Isolationsversuche bei Mykobakterien (M. lepraemurium, M. lepraefelis und M. tarwinense) erfolglos und die Erregerspezifizierung wurde mittels PCR durchgeführt (25)(26)(27).…”
Section: Therapie Und Verlaufunclassified
“…1,2 It has been demonstrated that approximately 1% of all feline biopsies submitted for histopathological analysis show changes consistent with mycobacteriosis (pyo/granulomatous inflammation dominated by epithelioid macrophages) and at least one-third of these have demonstrable Ziehl-Neelsen (ZN)-positive organisms when stained, with a thin rodlike appearance, indicative of mycobacteria; these are also referred to as acid-or alcohol-fast bacilli (AFB). [3][4][5] Clinically, about a third of feline mycobacteriosis cases in the UK are caused by Mycobacterium tuberculosis complex (MTBC) pathogens, with Mycobacterium microti being cultured from 19% of all cases of feline mycobacteriosis, and a further 15% caused by Mycobacterium bovis. 6,7 There is a strong geographical predisposition to feline infections with members of the MTBC.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, the significance of this disease has resulted in extensive biomedical research interest and, due to the growing threat of drug resistance, TB is a major focus of collaborative global healthcare investment 4 8 . Meanwhile, TB in domestic cats receives relatively little research attention, despite being more common and clinically significant than previously thought 9 11 . In the UK, approximately 1% of all feline biopsies submitted for routine histopathological analysis show changes consistent with mycobacteriosis and a third of these contain Ziehl-Neelsen (ZN) positive organisms when stained, with morphology indicative of the presence of mycobacteria 10 , 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The various mycobacterial species that have been identified in companion animals, including cats, can be grouped into the same two major categories as human mycobacterial disease; those belonging to the Mycobacterium tuberculosis- complex (MTBC) and the non-tuberculous mycobacteria (NTM, also referred to as ‘atypical mycobacteria’ or ‘mycobacteria other than tuberculosis’, MOTT) 11 , 13 – 19 .…”
Section: Introductionmentioning
confidence: 99%